2023
DOI: 10.1021/acsami.3c05121
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Infrared Photodetectors with Ultra-High Speed and Detectivity Based on Amorphous Cu-Based MOF Films

Shuangyin Gao,
Yi Huang,
Jin Tan
et al.

Abstract: Amorphous metal−organic frameworks (aMOFs) start to challenge their crystalline equivalents due to their unique advantages, like lack of grain boundaries, isotropy, flexibility, numerous defects-induced active sites, etc. However, aMOFs are typically synthesized under rigorous conditions, and their properties and applications need to be further explored. In this work, highly transparent p-type amorphous Cu-HHTP films consisting of Cu 2+ and 2,3,6,7,10,11-hexahydroxytriphenylene (HHTP) were synthesized using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…6 However, according to our research, only a few studies have reported MOFs as photoabsorption materials in solid-state PDs owing to the difficulty of integrating 3D porous MOFs into 2D optoelectronics. 4,7–11 In most applications for photon energy-to-electrical energy conversion, organic linkers with tunable bandgaps (2.69–3.9 eV) are responsible for generating electron–hole pairs when exposed to the visible-near infrared (Vis-NIR) spectrum, while MOCs with wide bandgaps (≥4 eV) are responsible for generating deep-UV electron–hole pairs. 12 Additionally, MOCs exhibit ultrahigh stability at ambient temperatures (up to 200 °C) and short wavelengths (up to 13.5 nm).…”
Section: Introductionmentioning
confidence: 99%
“…6 However, according to our research, only a few studies have reported MOFs as photoabsorption materials in solid-state PDs owing to the difficulty of integrating 3D porous MOFs into 2D optoelectronics. 4,7–11 In most applications for photon energy-to-electrical energy conversion, organic linkers with tunable bandgaps (2.69–3.9 eV) are responsible for generating electron–hole pairs when exposed to the visible-near infrared (Vis-NIR) spectrum, while MOCs with wide bandgaps (≥4 eV) are responsible for generating deep-UV electron–hole pairs. 12 Additionally, MOCs exhibit ultrahigh stability at ambient temperatures (up to 200 °C) and short wavelengths (up to 13.5 nm).…”
Section: Introductionmentioning
confidence: 99%